Breathing mode influence on craniofacial development and head posture - Annel Chambi‐Rocha; Ma Eugenia Cabrera‐Domínguez; Antonia Domínguez‐Reyes (Brazilian Society of Pediatrics, 2018)
Objective: The incidence of abnormal breathing and its consequences on craniofacial development is increasing, and is not limited to children with adenoid faces. The objective of this study was to evaluate the cephalometric differences in craniofacial structures and head posture between nasal breathing and oral breathing children and teenagers with a normal facial growth pattern. Method: Ninety‐eight 7-16 year‐old patients with a normal facial growth pattern were clinically and radiographically evaluated. They were classified as either nasal breathing or oral breathing patients according to the predominant mode of breathing through clinical and historical evaluation, and breathing respiratory rate predomination as quantified by an airflow sensor. They were divided in two age groups (G1: 7-9) (G2: 10-16) to account for normal age‐related facial growth. Results: Oral breathing children (8.0 ± 0.7 years) showed less nasopharyngeal cross‐sectional dimension (MPP) (p = 0.030), whereas other structures were similar to their nasal breathing counterparts (7.6 ± 0.9 years). However, oral breathing teenagers (12.3 ± 2.0 years) exhibited a greater palate length (ANS‐PNS) (p = 0.049), a higher vertical dimension in the lower anterior face (Xi‐ANS‐Pm) (p = 0.015), and a lower position of the hyoid bone with respect to the mandibular plane (H‐MP) (p = 0.017) than their nasal breathing counterparts (12.5 ± 1.9 years). No statistically significant differences were found in head posture. Conclusion: Even in individuals with a normal facial growth pattern, when compared with nasal breathing individuals, oral breathing children present differences in airway dimensions. Among adolescents, these dissimilarities include structures in the facial development and hyoid bone position.